A Scythian Ares (Aesch. Ch. 161–162)? - Musbakhova, Viktoria T. (Hyperboreus, 2019)
After a survey of multiple textual problems of Aesch. Ch. 161 f., the author proposes (1) to accept the scribe’s correction Σκύθης for the nonsensical manuscript σκυθιτα, (2) to retain the manuscript reading ῎῎Αρης, which is to be combined with Σκύθης, and (3) to read ἔργῳ, instead of ἐν ἔργῳ, which results in the following restoration of the text: …Σκύθης τ’ ἐν χεροῖν / παλίντον’ ἔργῳ βέλη ’πιπάλλων ῎Αρης (do / ia cr do). The Scythian Ares, who ﬁnds a parallel at Aesch. Pers. 85: τοξόδαμνον ῎Αρη, is to be understood as a Scythian warrior, i. e. an archer, who would thus be juxtaposed with a spearman. As a result, the sentence (Ch. 160–163) has two subjects and may be interpreted as the chorus’ appeal to a spearman and a Scythian archer to come together as rescuers of the house of Agamemnon. This pairing can be paralleled in Archaic Attic depictions of heavily armed warriors and archers in Scythian attire acting together in battle or marching in pairs – depictions that evoke the virtual world of epic battles as it is known from the Iliad, where spearmen and archers also ﬁght side by side. The chorus’ summoning of this pair of warriors as a combined symbol of epic warfare should be understood along the lines of the ironical treatment of the theme of a future avenger in the Parodos, where Aeschylus does his best not to connect the retaliation of Agamemnon’s death with Orestes until, at a later point, he reveals his mission as his father’s avenger. Besides, this pairing anticipates the joint role that Orestes and Pilades play in fulﬁlling Apollo’s order.